Health & Social Care (Adults) - Nolan, Yvonne (Harlow Heinemann, 2011)
Heinemann offers a total solution for those taking and delivering the new Level 3 qualification in Health and Social Care, supporting you in your qualification so that you in turn can support others. Written by Yvonne Nolan, our resources lead you down the pathway to success, and help you achieve healthy results.
Include Glossary, Index and Color Illustration
Keywords: Social service--Examinations -- Nurses' aides -- National Vocational Qualifications (Great Britain)